Home a memoir of my early years - Andrews, Julie 1935- (Hyperion, 2008)
Since her screen debut in Mary Poppins, Julie Andrews has played a series of memorable, endearing roles. But she has never told the story of her life before fame--until now. Here, she takes her readers on a warm, moving, and often humorous journey from a difficult upbringing in war-torn Britain to the brink of international stardom in America. Her memoir begins in 1935, when Julie was born to an aspiring vaudevillian mother and a teacher father, and takes readers to 1962, when Walt Disney himself saw her on Broadway. Along the way, she weathered the London Blitz; her parents' painful divorce; her mother's turbulent second marriage to Canadian tenor Ted Andrews, and a childhood spent on radio, in music halls, and giving concert performances all over England. Julie's professional career began at the age of twelve, and at eighteen, she left home for the United States to make her Broadway debut.--From publisher description